SHADOWING MAGIC: AN AMAZING LANGUAGE LEARNING TECHNIQUE IN TEACHING SPEAKING TO NON ENGLISH DEPARTMENT STUDENTS - Mike Amelia (ELP (Journal of English Language Pedagogy), 2020)
The objective of this study was to improve the speaking ability of non-English department students of Universitas Singaperbangsa Karawang (UNSIKA)by using the shadowing technique. The method of this research was Classroom Action Research (CAR) that was conducted to the PJKR (Pendidikan Jasmani Kesehatan dan Rekreasi) students at second grade of UNSIKA. The subject of the research consists of twenty-five students. The instruments are spoken test and observation guidelines. The research design applied in this study was a collaborative classroom action research consisting of 2 cycles covering 3 meetings for each cycle. The findings of this study showed the improvement of the students’ speaking ability from the first to the second cycle has improved highly. Where the mean score of vocabulary terms was 2 for the pre-cycle test become 3.28 for the second cycle post-test. Besides that, the mean score of grammar in the pre-cycle test was 1.84 increase 3.08 in the second cycle post-test. Same as the pronunciation term, the student's scores from the pre-cycle test to the second cycle test came up from 1.96 to 3.04. Furthermore, for the students speaking accuracy and fluency, their score also increase from 1.44 became 2.92. This research was successful to improve the students speaking ability by using the shadowing technique.